Extending the limits of transcatheter closure of atrial septal defects with the double umbrella device (CardioSEAL). Issue 1 (1st July 1998) - Kaulitz, R; Paul, T; Hausdorf, G
Abstract : Objective: To report initial findings from a selected group of patients with morphological variations of the atrial septal defect who underwent transcatheter closure with a second generation redesigned double umbrella device. Patients: Two patients with abnormal location of the oval fossa and partial deficiency of the septal rim, three patients with multiple defects, and two patients with a multiperforated aneurysm of the interatrial septum (age range, 3.6–25.5 years). Methods: Defects were closed with the double umbrella device (CardioSEAL) consisting of two sets of flexible arms (with central and two mid-arm hinges) covered with sewn Dacron patches. The implantation procedure was monitored by transoesophageal echocardiography. Results: The diameter of the defect measured during transoesophageal echocardiography ranged from 7–18 mm and the balloon stretched diameter ranged from 13–21 mm. The size of the devices varied from 28–33 mm and the ratio of device size to defect size varied from 1.6–2.1. Two devices (23 and 28 mm) were chosen in a patient with two separated defects. No complications or serious arrhythmias were observed during implantation or follow up (median, 1.8 months). Residual shunting was trivial in three patients and mild in one patient (inferiorly located additional defect). Conclusions: To extend the selection critera of an isolated central interatrial defect for transcatheter closure, some modifications of the implantation technique are needed. Using the redesigned double umbrella device, effective closure in patients with multiple or irregularly shaped atrial septal defects was achieved, indicating a broadening of the spectrum of transcatheter closure.